Diseño conceptual de un radio receptor y antena operando a longitudes de onda milimétricas para la observación de TeV Blazares desde el Observatorio Astronómico Nacional de San Pedro Mártir - Chaves-Jiménez, Nicole (Instituto Tecnológico de Costa Rica, 2018)
Blazars are one of the most important sources of energy in the universe. To understand the physical processes that take place in them, you need to get information in as many wavelengths as possible. Currently, in the National Astronomical Observatory operated by the Institute of Astronomy of the National Autonomous University of Mexico, it makes observations of the TEV-Blazars in the optical and in the near future in gamma radiation; but to understand in a better way the processes that surround these celestial objects, the idea of observing them in radius at wavelengths of millimeters is encouraged. This thesis consists of the conceptual design of a radio telescope for the detection of TEV-Blazares with the highest emission in radius at millimeter lengths. For this, radio telescope parameters were considered as angular resolution, gain, noise temperature and receiver sensitivity. The case of a simple antenna with the antenna and available receivers was analyzed, but as its parameters were not enough, a study with a two-antenna interferometer was made. To avoid possible errors in the observations with a two-antenna system, a three-antenna interferometer is proposed to perform the phase lock, for which the parameters for a three-antenna interferometer were determined.
Proyecto de Graduación (Licenciatura en Ingeniería Electrónica) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Electrónica, 2018.
Keywords: Radio; Astronomía; Blazares; Interferometría; Research Subject Categories::TECHNOLOGY::Electrical engineering, electronics and photonics::Electronics